Effectiveness of antimicrobial cocktails in primary isolation of Leptospira from bovine clinical samples - Pereira, P. V.; Brasil, T.; Loureiro, A. P.; Correia, L.; Pires, B. C.; Figueiredo, L.; Martins, G.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Isolation of leptospires from clinical samples is a challenge since presence of other microorganisms impairs leptospiral growth. Such contaminating bacteria deplete nutrients and produce metabolites that lead to inhibition of leptospires development.